What Place Takes Place in Jordan Abel’s The Place of Scraps ? - Claire Omhovère (Sillages Critiques)
Jordan Abel’s The Place of Scraps (2013) addresses the interrogations faced by those who grew up deprived of the language, beliefs and memories of their ancestors as a result of the cultural genocide perpetrated against the Indigenous peoples of North America to whom his first collection of poems is dedicated. Because Abel’s primary material comprises texts and images that have been widely circulated as first-hand knowledge about the Pacific Northwest, his compositions expose the discursive layers that inform Euro-Canadian representations of aboriginal places, particularly the enduring fascination for the totem pole’s interlacing of lineage, spirituality and territory in the place it indicates.